Exploiting WEE1 kinase activity as FUS: :DDIT3-dependent therapeutic vulnerability in myxoid liposarcoma - Heinst, Lorena; Lee, Kwang Seok; Berthold, Ruth; Isfort, Ilka; Wosnig, Svenja; Kuntze, Anna; Hafner, Susanne; Altvater, Bianca; Rossig, Claudia; Åman, Pierre; Wardelmann, Eva; Scholl, Claudia; et al. (Clinical cancer research, 2024)
The pathognomonic FUS::DDIT3 fusion protein drives myxoid liposarcoma (MLS) tumorigenesis via aberrant transcriptional activation of oncogenic signaling. As FUS::DDIT3 has so far not been pharmacologically tractable to selectively target MLS cells, this study investigated the functional role of the cell cycle regulator WEE1 as novel FUS::DDIT3-dependent therapeutic vulnerability in MLS.Immunohistochemical evaluation of the cell cycle regulator WEE1 was performed in a large cohort of MLS specimens. FUS::DDIT3 dependency and biological function of the G1/S cell cycle checkpoint were analyzed in a mesenchymal stem cell model and liposarcoma cell lines in vitro. WEE1 activity was modulated by RNAi-mediated knockdown and the small molecule inhibitor MK-1775 (adavosertib). An established MLS cell line-based chicken chorioallantoic membrane model was employed for in vivo confirmation.We demonstrate that enhanced WEE1 pathway activity represents a hallmark of FUS::DDIT3-expressing cell lines as well as MLS tissue specimens and that WEE1 is required for MLS cellular survival in vitro and in vivo. Pharmacologic inhibition of WEE1 activity results in DNA damage accumulation and cell cycle progression forcing cells to undergo apoptotic cell death. In addition, our results uncover FUS::DDIT3-dependent WEE1 expression as an oncogenic survival mechanism to tolerate high proliferation and resulting replication stress in MLS. Fusion protein-driven G1/S cell cycle checkpoint deregulation via overactive Cyclin E/CDK2 complexes thereby contributes to enhanced WEE1 inhibitor sensitivity in MLS.Our preclinical study identifies WEE1-mediated replication stress tolerance as molecular vulnerability in FUS::DDIT3-driven MLS tumorigenesis that could represent a novel target for therapeutic intervention.